Women and space in masjid architecture: Patterns, principles & perspectives - Mohd Nawawi, Norwina; Abdul Rahim, Zaiton; Abdul Majid, Noor Hanita; Jahn Kassim, Puteri Shireen (MPH Group Printing (M) Sdn Bhd, 2016)
This chapter address concerns of spaces for women in masjid. The chapter discussed the various hadiths that provide ample reason why women are part of the masjid environment although women are not compulsory to attend congregational prayers in the masjid as Men. Spaces that include entry and exit were explored through case studies. Findings showed the current trend in both traditional and modern masjid that provides spaces for women insignificantly. Recommendations include sensitivity of the architect to enquire from women themselves what they need and how new designs should incorporated spaces that are condusive in their submission to the Al-mighty.